Tegasan ricih di dalam pengangkutan endapan betung ribut - Ramli Mat Suki, (1990)
The critical shear stress approach is an alternative approach in storm sewer design. Analysis is conducted on this approach as a criterion in sediment transport in storm sewer and subsequently compared to the velocity approach. Comparison made showed that the critical shear stress method gives higher velocity than the velocity approach. The difference in assessing the shear stress is the main reason for this approach to produce high velocity